Chromium(III)-catalyzed addition of water and alcohol to α,β-unsaturated ketones for the synthesis of β-hydroxyl and β-alkoxyl ketones in aqueous media - Yun, Jin-Jin (2020)
An efficient chromium(III) chloride-catalyzed Michael-type reaction of water or alcohol with α,β-unsaturated ketones is developed. A variety of α,β-unsaturated ketones effectively reacted with either water or alcohols to give the corresponding β-hydroxyl ketones or β-alkoxyl ketones in modest to high yields with excellent compatibility to various functional groups. The approach was further utilized for the preparation of synthetically useful compounds containing tetrahydrofuran skeleton.